Arboreal Collective - (:unkn) unknown (My University, 2026)
The Arboreal Collective is a collaborative team of artists, Nina Sumarac, Nicos Synnos, and Xristos Panagiotou. It was formed in 2021with a focus on developing contemporary art projects that take a critical approach to social and environmental issues. (https://www.ninasumarac.com/arborealcollective, https://www.facebook.com/arborealcollectiveteam)